The association between neighborhood greenness and weight status: An observational study in Perth Western Australia - Pereira, Gavin; Christian, H.; Foster, S.; Boruff, B.; Bull, F.; Knuiman, M.; Giles-Corti, B. (2013)
Background: Few studies have examined the relationship between weight status and objectively measured neighborhood greenness and no study has examined this relationship across the different stages of adulthood. This research was an investigation of weight status and neighborhood greenness using objectively measured satellite remote sensing for a large population representative sample. Method. Cross-sectional study of 10,208 young adults (16-24 years), mid-age adults (25-64 years) and older adults (65+ years) from a population representative sample for the period 2004-2009 in Perth, Western Australia. Neighborhood greenness was ascertained for a 1600m road network service area around each participant's address using the mean and standard deviation of the Normalized Difference Vegetation Index (NDVI) obtained from remote sensing. Multiple logistic regression was used to assess associations with weight status (overweight-or-obese, obese) adjusted for socio-demographics and health-related behaviors. Results: The adjusted odds ratio (OR) comparing obesity in the highest to the lowest tertile of mean greenness was 0.78 (95% CI 0.69-0.89). For the same comparison, the OR for overweight-or-obese was similar, 0.84 (95% CI 0.76-0.92). The OR comparing obesity in the highest to lowest tertile of variation in greenness was 0.75 (95% CI 0.66-0.85). For the same comparison, the OR for overweight-or-obese was similar, 0.75 (95% CI 0.68-0.82). Conclusion: Higher levels and greater variation of neighborhood greenness are associated with lower odds of obesity among adults of all ages. Research examining neighborhood characteristics correlated with variability in greenness will help better understand these relationships. © 2013 Pereira et al.; licensee BioMed Central Ltd.